MEREDAM IDEOLOGI RADIKAL DI INDONESIA MELALUI PRAKTIK KETELADANAN NILAI PANCASILA - Maimun, Maimun (Sawala : Jurnal Administrasi Negara, 2015)
People's lives are driven by the basic idea of a foundation to fight for his life. The basic idea was referred to as an ideology, which dinyakini by a community or group as kosep ideal to strive for. In this world, there are two basic types of ideology, which is open and closed, and each country is based on the assurance ideology continue to be preserved. However, in addition to ideolgi countries, there are also other ideologies that are living within the individual which we refer to as personal ideology, and live in groups or as we say communal ideology. Radical ideology as a form of accumulation of trust on personal ideology was developed and dinyakini as a truth, that this ideology into the ideology of communal deliberately continue to be developed and championed by groups menyakininya. The group's ideology is contrary to Pancasila as the state ideology, and ways are being made to fight the ideology threatens people's lives and integrity of the country. This paper aims to describe the efforts made to curb radical ideology through exemplary education. With the approach of the description, this paper adopts literature references juxtaposed with reality. In addition to the observation in reality, this paper also disadurkan reference libraries by lifting the state ideology as a national consensus as well as a comparison against the ideology of personal and communal dinyakini and championed by some kelompo. The end of this paper the authors suggest the need for optimization and actualization exemplary approach in an effort to curb radical ideology in Indonesia, which has the potential to live and thrive in the community, particularly areas that are still dominated by the nationalist ethno culture, such as Aceh, Papua, Kalimantan and some Another area in Sumatra and even regions of the island of Java, as well as other community organizations in Indonesia.